2016
DOI: 10.1249/mss.0000000000000823
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Endurance Performance by Periodization of Carbohydrate Intake

Abstract: Short-term periodization of dietary CHO availability around selected training sessions promoted significant improvements in submaximal cycling economy, as well as supramaximal cycling capacity and 10-km running time in trained endurance athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
165
6
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(192 citation statements)
references
References 33 publications
13
165
6
8
Order By: Relevance
“…The NYT science writer interviewed the principal author of this paper, Dr. Laurie-Ann Marquet, about one of the studies in her doctoral program at the National Institute of Sport in Paris (INSEP). The investigation found that a group of triathletes who periodized their intake of carbohydrate during three weeks of training made performance gains not seen when a matched group did the same training and consumed a similar total amount of carbohydrate, but spread equally over the day (Marquet et al 2016). The intervention was implemented on three days of each week, and involved shifting all dietary carbohydrate on these days to the period between the morning (moderate intensity) and afternoon (high intensity intervals) training sessions so that the quality session was undertaken with high carbohydrate availability, while restoration of glycogen was postponed until after the next morning's recovery session to promote prolonged adaptation from the first session and increased metabolic stress in the second (Bartlett et al 2015).…”
Section: Public Distrust Of Industry-supported Researchmentioning
confidence: 99%
“…The NYT science writer interviewed the principal author of this paper, Dr. Laurie-Ann Marquet, about one of the studies in her doctoral program at the National Institute of Sport in Paris (INSEP). The investigation found that a group of triathletes who periodized their intake of carbohydrate during three weeks of training made performance gains not seen when a matched group did the same training and consumed a similar total amount of carbohydrate, but spread equally over the day (Marquet et al 2016). The intervention was implemented on three days of each week, and involved shifting all dietary carbohydrate on these days to the period between the morning (moderate intensity) and afternoon (high intensity intervals) training sessions so that the quality session was undertaken with high carbohydrate availability, while restoration of glycogen was postponed until after the next morning's recovery session to promote prolonged adaptation from the first session and increased metabolic stress in the second (Bartlett et al 2015).…”
Section: Public Distrust Of Industry-supported Researchmentioning
confidence: 99%
“…An emerging 439 theme in exercise physiology is the augmentation of endurance-type training adaptations through 440 manipulation of substrate availability. Methods such as multiple bouts of exercise (79,80) , 441 reductions in dietary carbohydrate intake and timing of dietary carbohydrate intake (81,82) and during exercise can attenuate and/or abolish the increases in VO2max (83) glucose tolerance,…”
mentioning
confidence: 99%
“…Kombinace večerního (bez následné regenerace glykogenu) a ranního tréninku nalačno snižuje endogenní i exogenní SD a patří mezi novinky ve světě sportovní výživy. Tento koncept spadající do train-low strategie přitahuje odbornou pozornost a první výsledky pilotních metodologicky precizně propracovaných prací jsou více než slibné (Lane et al, 2015;Marquet et al, 2016).…”
Section: "Sleep Low" Strategieunclassified